The Compatibility between Grounded Theory and Library Practitioner Research Problems - Fraser-Arnott, Melissa (Qualitative and Quantitative Methods in Libraries, 2019)
The selection of an appropriate research methodology is an important step in any research project. This article argues that the Grounded Theory (GT) methodology is compatible with the values and research interests of the library and information science (LIS) research community. Compatibilities are identified between librarianship and Grounded Theory along five themes. These themes are (1) the relationship between librarianship’s interdisciplinary nature and GT’s theoretical neutrality; (2) librarianship’s client-centeredness and GT’s focus on participants’ main concern; (3) the connection between evidence based library and information practice and GT’s inductive focus on grounding results in data, (4) the complexity of problems in librarianship, and (5) the need for generalizability of findings across various types of library environments. These compatibilities should lead researchers about to investigate academic or practitioner research projects in the LIS field to consider this methodology as a viable research option.